Ticagrelor or Prasugrel in Patients With Non–ST-Segment Elevation Acute Coronary Syndromes - Valina, Christian; Neumann, Franz-Josef; Menichelli, Maurizio; Mayer, Katharina; Woehrle, Jochen; Bernlochner, Isabell; Aytekin, Alp; Richardt, Gert; Witzenbichler, Bernhard; Sibbing, Dirk; Cassese, Salvatore; Angiolillo, Dominick J.; et al. (Journal of the American College of Cardiology, 2020)
Background: Current guidelines recommend intensified platelet inhibition by prasugrel or ticagrelor in patients with unstable angina (UA) or non-ST-segment elevation (NSTE) myocardial infarction (MI). Objectives: This study sought to investigate the benefits and risks of ticagrelor as compared with prasugrel in patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS) and planned invasive management. Methods: This post hoc analysis combines the pre-specified subgroups of UA and NSTEMI of the randomized ISAR-REACT 5 trial. It included 1,179 patients assigned to ticagrelor and 1,186 assigned to prasugrel. Ticagrelor was started immediately after randomization and prasugrel after coronary angiography. The primary endpoint was a composite of death, MI, or stroke during 1-year follow-up, and the safety endpoint was Bleeding Academic Research Consortium class 3–5. Results: The primary endpoint was reached in 101 (8.7%) patients in the ticagrelor and in 73 (6.3%) patients in the prasugrel group (hazard ratio [HR]: 1.41; 95% confidence interval [CI]: 1.04 to 1.90). The HR for all-cause death was 1.43 (95% CI: 0.93 to 2.21) and that for MI 1.43 (95% CI: 0.94 to 2.19). The safety endpoint occurred in 49 (5.2%) patients in the ticagrelor and in 41 (4.7%) patients in the prasugrel group (HR: 1.09; 95% CI: 0.72 to 1.65). Landmark analysis revealed persistence of the efficacy advantage with prasugrel after the first month. Conclusions: In patients with NSTE-ACS, we found that prasugrel was superior to ticagrelor in reducing the combined 1-year risk of death, MI, and stroke without increasing the risk of bleeding. Due to the post hoc nature of the analysis, these findings need confirmation by further studies. (Prospective, Randomized Trial of Ticagrelor Versus Prasugrel in Patients With Acute Coronary Syndrome; NCT01944800)
CRIS-Team Scopus Importer:2023-03-08
Keywords: mortality; non-ST-segment elevation acute coronary syndrome; percutaneous coronary intervention; prasugrel; ticagrelor